Different methods of determining centric relation - comparison with a digital mandibular motion analyser - Bálint Jász; Szilvia Ambrus; Tamás Garay; Péter Schmidt; Péter Hermann; Szandra Körmendi; Máté Jász (BMC, 2024)
Abstract Background Finding and registering the maxillary-mandibular jaw relation is crucial in dental practice. Several comparative studies have been conducted to investigate the reproducibility and accuracy of techniques for determining the centric relation (CR) position of the mandible. The aim of our study was to determine which of seven different CR determination methods had the smallest deviation from the theoretical zero with the help of a digital mandibular motion analyser. The chosen theoretical zero position, the maximal intercuspal position (MIP), is the most reproducible and widely used position. Methods Thirty-four volunteers (24 females and 10 males) with a mean (SD) age of 29.1 (± 7.3) years with a negative history of temporomandibular disorder (TMD) participated in the study. A digital mandibular motion analyser was used to register the condylar position after the use of each technique for the determination of CR. The calibration was performed to the maximal intercuspal position (MIP) for each volunteer. The investigated techniques were (A) the gothic arch tracer, (B) the adduction field method, (C) Dawson's bimanual manipulation, (D) the patient placing the tongue tip on the palatal rugae, (E) the patient placing the tongue tip to the border of the hard and soft palate, (F) the patient actively pulling the chin backwards, and (G) the examiner pushing the patient's chin back. Results The position of the mandibular condyle was illustrated in a three-dimensional coordinate system, where the origin represented the MIP. Among the seven methods examined, five showed significant deviations compared to the MIP. Among these, two methods resulted in posterior deviation of the condyles. Methods C and E coincided with the MIP in all directions. Conclusions Within the limitations of our study, we found that the smallest deviations from our theoretical zero (MIP) among the investigated centric relation determining methods were obtained with the bimanual mandibular manipulation technique derived from Dawson and the placement of the tongue tip on the border of the hard and soft palate (linguomandibular homotrophy theory).